Hubungan Antara Adopsi Teknologi Pemanenan Terhadap Tingkat Pendapatan Petani Padi Sawah (Studi Kasus di Kabupaten Kolaka, Sulawesi Tenggara) - Prihantini, Campina Illa; Syahrir, Syahrir; Irna, Irna; Masitah, Masitah (Fakultas Pertanian, Universitas Timor, 2024)
The purpose of the study was to examine the differences in the amount of labor costs, farm costs and income of paddy fields with Combine Harvester and Power Thresher harvesting technology in Lamedai Village, Tanggetada District, Kolaka Regency. The method of taking the number of samples by proportionate Stratified Random Sampling method and for the determination of the type of sample by Simple Random Sampling method as many as 52 samples. Each farmer who did farming with Combine Harvester harvesting technology as many as 29 samples and Power Thresher as many as 23 samples. The method of data analysis used in this study is the analysis of different test model independent sampleT-test. The results showed that there was a significant difference in total farming costs and rice revenues with Combine Harvester and Power Thresher harvesting technology in Lamedai Village, Tanggetada District, Kolaka Regency. The results showed that there is a real difference in income received by farmers who use power trasher machine with combine harvester. However,both still provide benefits and deserve to continue their business because the value of RC and BC ratio is positive. The suggestion that can be recommended is that farmers can be more familiar with the combine harvester machine so that the productivity of rice land is higher which also affects the income received by farmers.